Patient- and provider-related determinants of generic and specific health-related quality of life of patients with chronic systolic heart failure in primary care: a cross-sectional study - Peters-Klimm, Frank; Kunz, Cornelia Ursula; Laux, Gunter; Szecsenyi, Joachim; Müller-Tasch, Thomas (Health and quality of life outcomes, 2010)
Identifying the determinants of health-related quality of life (HRQOL) in patients with systolic heart failure (CHF) is rare in primary care; studies often lack a defined sample, a comprehensive set of variables and clear HRQOL outcomes. Our aim was to explore the impact of such a set of variables on generic and disease-specific HRQOL.